2012
DOI: 10.1021/ja3057562
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Mapping of Osteopontin Adsorption to Calcium Oxalate Monohydrate Crystals by Tip-Enhanced Raman Spectroscopy

Abstract: In the ectopic biomineralization of calcium oxalate kidney stones, the competition between calcium oxalate monohydrate (COM) formation and its inhibition by the phosphoprotein osteopontin (OPN) plays a key role in COM stone-forming processes. To get more insights into these processes, tip-enhanced Raman spectroscopy (TERS) was used to provide surface-specific information about the adsorption of OPN to faces of COM crystals. In TERS, the surface plasmon resonance of a metallic AFM tip is locally excited when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…Opilik et al demonstrated imaging of two-phase lipid domains with STM-TERS (Figure 29 (b)) [368]. Kazemi-Zanjani et al were able to image phosphoprotein osteopontin on calcium oxalate monohydrate crystal facets (relevant to the breakup of kidney stones), with sufficient resolution to observe preferential adherence to the edge facets of the crystal [369].…”
Section: Applicationsmentioning
confidence: 99%
“…Opilik et al demonstrated imaging of two-phase lipid domains with STM-TERS (Figure 29 (b)) [368]. Kazemi-Zanjani et al were able to image phosphoprotein osteopontin on calcium oxalate monohydrate crystal facets (relevant to the breakup of kidney stones), with sufficient resolution to observe preferential adherence to the edge facets of the crystal [369].…”
Section: Applicationsmentioning
confidence: 99%
“…1.5; diameter: 10 mM ), using 200 µl of 50 mM HEPES, 150 mM NaCl, pH 7.4, at 37 °C. Raman spectra were taken directly from the in situ-grown crystals as previously described (Hug et al 2012;Kazemi-Zanjani et al 2012). To this end, a LabRAM HR spectrometer (Horiba-Jobin-Yvon Scientific, Edison, NJ, USA) provided with a 632.8 nm excitation laser was connected to an Olympus IX71 inverted optical microscope (Olympus Corporation, Tokyo, Japan).…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…rat bone, rat kidney, bovine milk) have shown a strong and irreversible adsorption to COM crystal faces [10,[22][23][24], which resulted in the hindrance of propagating crystals steps [25], in the inhibition of three-dimensional growth [10,26] and in the incorporation of the protein into the crystal structure [23,27]. Nene et al have reported that an OPN phosphopeptide adsorbs at the crystal face in front of a growing step and hinders its growth, before it is integrated into the crystal structure and overgrown (after exchanging the protein containing solution by a control solution) by freshly crystallizing monohydrate phase [28].…”
Section: Introductionmentioning
confidence: 99%